Diagnosis of Patent Foramen Ovale: The Combination of Contrast Transcranial Doppler, Contrast Transthoracic Echocardiography, and Contrast Transesophageal Echocardiography. (25th February 2020) - Yang, Xiaoxue; Wang, Hua; Wei, Yajuan; Zhai, Nina; Liu, Baomin; Li, Xiaopeng
Abstract : Objectives . To access the distinct values of contrast transcranial Doppler (cTCD), contrast transthoracic echocardiography (cTTE), and contrast transesophageal echocardiography (cTEE) in the diagnosis of right-to-left shunt (RLS) due to patent foramen ovale (PFO) and to define the most practical strategy for the diagnosis of PFO. Methods . 102 patients with a high clinical suspicion for PFO had simultaneous cTCD, cTTE, and cTEE performed. The agitated saline mixed with blood was used to detect right-to-left shunt (RLS). Results . In all 102 patients, the shunt was detected at rest by cTCD in 60.78% of cases, by cTTE in 42.16%, and by cTEE in 47.06%. The positive results of all 3 techniques with Valsalva maneuver (VM) were significantly improved. cTCD showed higher pick-up rate than cTTE (98.04% vs. 89.22%; χ 2 = 12.452, p < 0.05 ) and the cTEE (98.04% vs. 96.08%; nonsignificant difference) in the diagnosis of PFO. Nevertheless, cTEE, compared with cTTE, underestimated shunting in 44% of patients. The diameter of both PFO entrance and exit was significantly greater in patients with a severe shunt compared with a mild shunt (2.8 ± 1.0 mm vs. 2.0 ± 0.7 mm, t = 3.135, p < 0.05 ; 2.2 ± 0.7 mm vs. 1.6 ± 0.4 mm, t = − 2.582, p < 0.05 ). There was a nonsignificant difference in tunnel length between patients with mild shunting and severe shunting(9.3 ± 2.7 mm vs. 9.4 ± 2.9 mm ; t = 1.358, p > 0.05 ). Conclusions . The best method to diagnose PFO should be the combination of cTCD, cTTE, and cTEE. And cTCD should be applied as the first choice for screening RLS. Then, cTTE should be performed to quantify the severity of the shunt. Last but not least, cTEE should be performed to assess the morphologies of PFO when the closure is planned. The study provides for clinicians the most practical strategy for diagnosing PFO in the future. However, further trials with a large sample size are required to confirm this finding.